San-Huang-Chai-Zhu Formula Ameliorates Liver Injury in Intrahepatic Cholestasis through Suppressing SIRT1/PGC-1α-Regulated Mitochondrial Oxidative Stress. (8th July 2022) - Liu, Binbin; Zhang, Jie; Shao, Lu; Yao, Jiaming
Abstract : Background . Chinese herbal formulae possess promising applications in treating intrahepatic cholestasis. Objective . Our study aims to explore the protective effect of the San-Huang-Chai-Zhu formula (SHCZF) on liver injury in intrahepatic cholestasis (IC) and investigate the underlying mechanism related to mitochondrial oxidative stress. Methods . An IC rat model was established by α -naphthyl isothiocyanate induction. Hepatic histomorphology was observed through hematoxylin and eosin staining. Levels of biochemical indexes of hepatic function and oxidative stress were determined by an enzyme-linked immunosorbent assay. Cell apoptosis in liver tissues was detected by the TUNEL assay. The mRNA expression of mtDNA, SIRT1, and PGC-1 α was measured by qRT-PCR, and the protein expression of Bax, Bcl-2, caspase-3, SIRT1, and PGC-1 α was determined by Western blotting. Results . SHCZF treatment attenuated liver injury in IC. Levels of hepatic function parameters were decreased after SHCZF administration. In addition, the decreased level of malondialdehyde (MDA) and the increased levels of superoxide dismutase (SOD), glutathione (GSH), and adenosine triphosphate (ATP) in hepatic mitochondria confirmed that SHCZF could attenuate oxidative stress in IC. SHCZF treatment also reduced the apoptosis in the liver tissues of IC rats. Furthermore, SHCZF administration upregulated the expression of mtDNA, SIRT1, and PGC-1 α in IC. Conclusions . SHCZF exerts a protective effect on liver injury in IC via alleviating SIRT1/PGC-1 α -regulated mitochondrial oxidative stress.